Teacher Comfort in Managing Asthma: A Two-State Study - Yvette Q. Getch; Ethan Schilling; Stacey M. Neuharth-Pritchett; Sofia Hirt (Allergies)
Background/Objectives: This study assessed teacher comfort in supporting the medical management of children with asthma in elementary and middle schools in two southern states in the U.S. Teacher comfort in asthma management is a largely underexplored area yet holds promise to support medical management in schools. Methods: Using survey methods, data were gathered from a random sample of teachers in two southern U.S. states (n = 574). Data from the Teacher Capability and School Resource Scale for Asthma Management scale were used to assess teacher comfort and capability in managing stressful asthma management episodes. Results: Teachers expressed comfort in supporting children with asthma in their classrooms. On the Teacher Capability in Social and Emotional Aspects of Asthma Management (SEAM) factor, the mean rating was 3.89 (SD = 0.83) out of 5, and the mean rating for the School Resources/Institutional Capability for Asthma Management factor was 3.77 (SD = 0.99) out of 5. Conclusions: The findings demonstrate that access to school, community, and medical resources; coordinated school-based asthma care plans; and pre-service preparation improve teacher comfort. School nursing support is needed for teacher education.